Does Mechanical Damage on Soybean Induces the Production of Flavonoids? - Júnior, Neilier Rodrigues da Silva; Barros, Rafael Almeida; Meriño-Cabrera, Yaremis Beatriz; Oliveira, Maria Goreti de Almeida (Current Approaches in Science and Technology Research Vol. 3, 2021)
The response of plants to grazing includes the production of chemical defense compounds such as proteases inhibitors and secondary metabolites as flavonoids, which makes them less palatable to feeding and negatively affecting the physiology of insects. This study aimed to evaluate the phytochemical response of soybean cultivars Glycine max resistant (IAC-17, IAC-24) and susceptible (IAC-P1) to insects after mechanical damage. These cultivars were mechanically injured, and after 24 hours samples of these plants were analyzed by HPLC to identify and quantify flavonoids. The flavonoids daidzein, quercetin, and rutin were quantified, with the highest concentration of daidzin in soybean cultivars after mechanical damage. Rutin was biosynthesized by IAC-24. The cultivars IAC-PL1, IAC-17, and IAC-24 did not show a flavonoid response to mechanical damage. The soybean cultivars are not dependent on mechanical damage to produce flavonoids.